International Porphyria Molecular Diagnostic Collaborative: an evidence-based database of verified pathogenic and benign variants for the porphyrias - Chen, Brenden (Genet Med, 2019)
With the advent of precision and genomic medicine, a critical issue is whether a disease gene variant is pathogenic or benign. Such is the case for the three autosomal dominant acute hepatic porphyrias (AHPs), including acute intermittent porphyria, hereditary coproporphyria, and variegate porphyria, each resulting from the half-normal enzymatic activities of hydroxymethylbilane synthase, coproporphyrinogen oxidase, and protoporphyrinogen oxidase, respectively. To date, there is no public database that documents the likely pathogenicity of variants causing the porphyrias, and more specifically, the AHPs with biochemically and clinically verified information. Therefore, an international collaborative with the European Porphyria Network and the National Institutes of Health/National Center for Advancing Translational Sciences/National Institute of Diabetes and Digestive and Kidney Diseases (NIH/NCATS/NIDDK)-sponsored Porphyrias Consortium of porphyria diagnostic experts is establishing an online database that will collate biochemical and clinical evidence verifying the pathogenicity of the published and newly identified variants in the AHP-causing genes. The overall goal of the International Porphyria Molecular Diagnostic Collaborative is to determine the pathogenic and benign variants for all eight porphyrias. Here we describe the overall objectives and the initial efforts to validate pathogenic and benign variants in the respective heme biosynthetic genes causing the AHPs.